(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Heavy metals such as Cu, Pb, Zn and Cd are ubiquitous in our environment and this study seeks to investigate the concentration of heavy metals in cassava tubers cultivated under high voltage electric power lines and thus assess the associated human health risk arising from its consumption in three communities in Aniocha South LGA, Delta State. Cassava tuber samples were collected from farm under the power lines using a spade. Standard laboratory procedures were adopted for determination of the concentration of heavy metals in the samples using Atomic Absorption Spectrophotometer (AAS). Results revealed that the concentration of heavy metals in the samples range from 7.350.05, 9.573.24, 0.840.43 and 0.220.08 mg/kg for Cu, Zn, Pb and Cd respectively. Bioaccumulation of heavy metals from soil to root revealed Zn 1 in samples across all sampled locations. The life carcinogenic risk value showed that consumption of cassava tubers cultivated under high voltage power lines in the sampled communities by the local populace are not under any immediate carcinogenic threat. However, THI revealed that continuous consumption of these cassava tubers may pose the emergence of carcinogenic threat.